2021
DOI: 10.1038/s41467-020-20790-0
|View full text |Cite
|
Sign up to set email alerts
|

MOTS-c is an exercise-induced mitochondrial-encoded regulator of age-dependent physical decline and muscle homeostasis

Abstract: Healthy aging can be promoted by enhanced metabolic fitness and physical capacity. Mitochondria are chief metabolic organelles with strong implications in aging that also coordinate broad physiological functions, in part, using peptides that are encoded within their independent genome. However, mitochondrial-encoded factors that actively regulate aging are unknown. Here, we report that mitochondrial-encoded MOTS-c can significantly enhance physical performance in young (2 mo.), middle-age (12 mo.), and old (22… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
136
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(141 citation statements)
references
References 82 publications
5
136
0
Order By: Relevance
“…Beyond steroidogenesis in the mitochondrial matrix, mitochondria contain their own genome from which small mtDNA-encoded peptides are synthesized (e.g., MOTS-c, humanin) ( Yen et al, 2020 ; Lee et al, 2015 ; Reynolds et al, 2020a ), and released in the systemic circulation in response to challenges to optimize metabolic regulation. Thus, mitochondria-derived signaling molecules – or mitokines – likely play a significant role in human physiology and stress adaptation ( Reynolds et al, 2020b ).…”
Section: The Rise Of Mitochondria In Psychopathologymentioning
confidence: 99%
“…Beyond steroidogenesis in the mitochondrial matrix, mitochondria contain their own genome from which small mtDNA-encoded peptides are synthesized (e.g., MOTS-c, humanin) ( Yen et al, 2020 ; Lee et al, 2015 ; Reynolds et al, 2020a ), and released in the systemic circulation in response to challenges to optimize metabolic regulation. Thus, mitochondria-derived signaling molecules – or mitokines – likely play a significant role in human physiology and stress adaptation ( Reynolds et al, 2020b ).…”
Section: The Rise Of Mitochondria In Psychopathologymentioning
confidence: 99%
“…As a new class of circulating signaling molecules, skeletal muscle-produced and -secreted MDPs could potentially be involved in training adaptation. Indeed, both mice and human participants showed increased MOTS-c expression in skeletal muscle as well as increased circulating levels upon acute endurance exercise ( Reynolds et al, 2021 ; Yang et al, 2021 ). Similarly, the MDP humanin increased in muscle and plasma of healthy young men following acute high-intensity cycling.…”
Section: Mitochondrial-derived Peptidesmentioning
confidence: 99%
“…However, the intracellular mechanisms regulating MDP production and secretion during exercise are still unknown, even though a responsiveness to signals associated with cellular energy stress occurring in exercised muscles is conceivable ( Merry et al, 2020 ). Moreover, despite the training-like effects of systemic MOTS-c treatment on endurance performance in mice ( Reynolds et al, 2021 ), the role and molecular targets of exercise-induced MDPs as well as their auto-, para- and endocrine relevance in mediating physiological training adaptation has yet to be established. Kumagai et al (2021) suggested that MOTS-c could act as a myostatin inhibitor by increasing Akt activity via activation of mTORC2 and inhibition of phosphatase and tensin homolog (PTEN) through casein kinase 2 (CK2) activation.…”
Section: Mitochondrial-derived Peptidesmentioning
confidence: 99%
“…Recent research has reported that MOTS-c translocates from mitochondria into the nucleus in response to glucose restriction, leading to retrograde signaling [ 118 , 184 ]. MOTS-c can bind to nuclear genomic DNA and interact with transcription factor Nrf2 to activate gene transcription, resulting in increased cellular resistance to metabolic stress [ 118 ].…”
Section: Emerging Regulators For 3d Architecture Of Mitochondrial Nucleoidmentioning
confidence: 99%
“…MOTS-c can bind to nuclear genomic DNA and interact with transcription factor Nrf2 to activate gene transcription, resulting in increased cellular resistance to metabolic stress [ 118 ]. Reynolds et al in 2021 found that MOTS-c is an exercise-induced mitochondrial-encoded regulator of muscle homeostasis which can regulate the nuclear genes involved in metabolism and proteostasis, thereby significantly improving physical performance in young, middle-aged, and old mice [ 184 ]. Moreover, administration of MTOS-c at late-life (23.5 months) can increase the lifespan of old mice.…”
Section: Emerging Regulators For 3d Architecture Of Mitochondrial Nucleoidmentioning
confidence: 99%